Composite positive electrode material, preparation method and all-solid-state battery

By combining lithium halide with high-nickel layered oxide positive electrode material in all solid state batteries, the problem of interface side reaction between the positive electrode and the sulfide electrolyte in the battery is solved, and the problem of significantly improved the The cycle stability and energy density of the battery are achieved.

CN119481012APending Publication Date: 2025-02-18JIANGSU UNIQUE ADVANCED MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411733437.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In all-solid state batteries, the interface side reaction between the high-nickel layered oxide positive electrode material and the sulfide electrolyte leads to poor cell circulation performance and the electrolyte is easy to decompose under high pressure.

Method used

The resonant acoustic mixing method is used to combine lithium halide with high nickel layered oxide positive electrode material to form a composite positive electrode material, and the ionic and electronic conductivity of the material is improved by annealing and resonant mixing treatment.

Benefits of technology

It effectively suppresses the side reaction between the positive electrode and the sulfide electrolyte, reduces the interface resistance, and improves the cycle stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160885210000071
    Figure BDA0005160885210000071
Patent Text Reader

Abstract

The invention discloses a composite positive electrode material, a preparation method and an all-solid-state battery. The preparation method comprises the following steps: weighing a lithium source and an AxBy raw material according to a stoichiometric ratio of (3-5): 1 under the protection of an argon atmosphere, pouring the weighed lithium source and AxBy raw material into a zirconium oxide tank filled with zirconium oxide balls according to a ball-to-material ratio of (15: 1)-(30: 1), and carrying out ball milling for 10-30 hours by using a planetary ball mill to obtain mixed powder; placing the mixed powder in a vacuum sealing furnace, annealing at 260-320 DEG C for 1-6 hours at the heating rate of 1-5 DEG C / min, and naturally cooling to room temperature after annealing treatment to obtain LiAB halide powder; and putting the NCM material and LiAB halide powder in a mass ratio of (90-99): (1-10) into a resonant mixer, treating the mixture at the acceleration of 30-100G, and carrying out resonant mixing for 0.5-3 hours to obtain the positive electrode material containing the halide protective layer. The composite positive electrode material with high ion and electron conductivity can be obtained, and a dynamically stable interface is realized in the positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of all-solid-state battery production, and in particular relates to a composite positive electrode material, a preparation method and an all-solid-state battery. Background technology:

[0002] All-solid-state batteries have attracted great attention due to their superior safety characteristics and advanced cell design, which can achieve higher energy density than current lithium-ion batteries. Sulfide electrolytes have higher ionic conductivity than liquid electrolytes and good mechanical properties, thus having significant advantages in all-solid-state battery composition. However, the battery cycling performance is mainly affected by the interface between the sulfide electrolyte and the high-nickel layered oxide particles, and the electrolyte is easily decomposed under high pressure.

[0003] At present, in order to reduce the high-voltage LiNi x Co y Mn z The interfacial side reactions of O2(NCM) cathode materials with sulfide electrolytes have been extensively studied using protective oxide coatings (e.g., LiNbO3 and Li2ZrO3). However, due to the electronic insulating properties and extremely low ionic conductivity (10 -6 -10 -9 S / cm), and the coating interface reaction kinetics are relatively slow. Therefore, how to obtain a composite cathode with high ionic and electronic conductivity to achieve a kinetically stable interface inside the cathode is crucial to mitigate the cathode / electrolyte interface problem in all-solid-state batteries.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0005] The object of the present invention is to provide a composite positive electrode material, a preparation method and an all-solid-state battery, so as to overcome the defects in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides a method for preparing a composite positive electrode material, the steps of which are: 1) under the protection of an argon atmosphere, weighing a lithium source, an A x B y Raw materials, wherein A is a metal cation and B is a halogen anion, weigh the lithium source, A x B y The raw materials are poured into a zirconia tank filled with zirconia balls, with a ball-to-material ratio of 15:1 to 30:1, and ball-milled for 10 to 30 hours using a planetary ball mill to obtain a mixed powder;

[0007] (2) placing the mixed powder obtained in step (1) in a vacuum sealed furnace, annealing at 260-320° C. for 1-6 h, with a heating rate of 1-5° C. / min, and naturally cooling to room temperature after the annealing treatment to obtain LiAB halide powder;

[0008] (3) placing the NCM material and the LiAB halide powder in a resonant mixer at a mass ratio of 90-99:1-10, treating the mixture at an acceleration of 30-100G, and the resonant mixing time is 0.5-3h to obtain a positive electrode material containing a halide protective layer.

[0009] Preferably, in the technical solution, the lithium source includes one or more of lithium chloride, lithium hydroxide, and lithium oxide.

[0010] Preferably, in the technical solution, the metal cation A includes Mg 2+ 、Al 3+ , Ga 3+ 、In 3+ , Sb 3+ 、Bi 3+ , Y 3+ Sc 3+ ,La 3 + 、Ce 3+ , Pr 3+ 、Nd 3+ 、Pm 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ 、Zr 4+ , Hf 4+ Cr 3+ , Fe 3+ 、Zn 2+ and Cd 2+ One or more of .

[0011] Preferably, in the technical solution, the halogen anion B includes one or more of Cl, Br, I or F.

[0012] A composite positive electrode material, characterized in that it is prepared by the above-mentioned composite positive electrode material preparation method.

[0013] A method for preparing an all-solid-state battery, comprising the following steps: (1) in an argon glove box, placing 100-150 mg of a sulfide electrolyte Li6PS5Cl (Crode) into a plastic sleeve with a diameter of 10-12 mm for a mold battery, and cold pressing and compacting it into a powder cake state at 180-220 MPa;

[0014] (2) 20 to 30 mg of the composite positive electrode active material powder is placed in the sleeve, and cold pressed at 280 to 320 MPa to form a positive electrode layer on the surface of the sulfide electrolyte, and a piece of aluminum foil with a thickness of 18 to 22 μm is stacked on the outside of the positive electrode layer, and the aluminum foil forms a current collector on the outside of the positive electrode layer;

[0015] (3) placing an indium sheet with a thickness of 80 to 120 μm and a lithium sheet with a thickness of 40 to 60 μm as a negative electrode layer on the opposite side of the side where the sulfide electrolyte contacts the positive electrode layer, and allowing the negative electrode layer to further contact the sulfide electrolyte layer under a pressure of 10 to 15 MPa to obtain a laminate consisting of a positive electrode layer, a sulfide electrolyte and a negative electrode layer in sequence; stacking a copper foil with a thickness of 5 to 12 μm on the outside of the negative electrode layer, and the copper foil forms a current collector on the outside of the negative electrode layer;

[0016] (4) Stainless steel current collectors are placed above and below the stack, and current collecting leads are attached to the stainless steel current collectors to obtain an all-solid-state battery.

[0017] An all-solid-state battery, characterized in that it is prepared using the above-mentioned all-solid-state battery preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] When bare NCM is in direct contact with sulfide electrolyte (LPSCl), due to the narrow electrochemical potential window of LPSCl, interfacial side reactions will occur during charging, and the byproducts will form a resistive interface, which will hinder the Li + The lithium halide is used as an interface regulator instead of a separator and electrode electrolyte material. Due to its high ionic / electronic conductivity, the side reaction between NCM and sulfide electrolyte (LPSCl) can be effectively suppressed, thus reducing the positive electrode interface resistance.

[0020] Compared with traditional mixing methods such as stirring and kneading, resonant acoustic mixing can achieve uniform mixing of solid-solid materials; the mixing efficiency is high, which is 2-10 times that of traditional mixing methods; there is no blade intervention, avoiding strong local stimulation of the mixed materials by the blade and the collision of the blade with the wall of the mixing container; it can be mixed in situ, realizing direct mixing of materials in the filling container, eliminating the material transfer and filling links; it does not require cleaning, there is no cleaning of mixing blades and transfer containers, and it is more environmentally friendly. Specific implementation method:

[0021] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0022] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0023] Example 1

[0024] A preparation method of a composite positive electrode material, comprising the following steps: (1) under the protection of an argon atmosphere, weighing LiCl and YbCl3 according to a stoichiometric ratio of 3:1, pouring the weighed LiCl and YbCl3 into a zirconia tank filled with zirconia balls, the ball-to-material ratio being 20:1, and using a planetary ball mill at a speed of 700 rpm for 15 h to obtain a mixed powder;

[0025] (2) placing the mixed powder obtained in step (1) in a vacuum sealed furnace, annealing at 300° C. for 3 h at a heating rate of 2° C. / min, and naturally cooling to room temperature after the annealing treatment to obtain Li3YbCl6 lithium halide powder;

[0026] (3) The positive electrode material LiNi with a particle size of 3 μm 0.83 Co 0.11 Mn 0.06 O2 and Li3YbCl6 lithium-conducting halide powders are placed in a resonant mixer at a mass ratio of 97:3, and resonantly mixed for 1 hour at an acceleration of 80G to obtain a positive electrode material containing a halide protective layer.

[0027] A composite positive electrode material is prepared by adopting the above preparation method.

[0028] Example 2

[0029] A method for preparing a composite positive electrode material, comprising the following steps: (1) under the protection of an argon atmosphere, weighing LiCl and InCl3 according to a stoichiometric ratio of 4:1, pouring the weighed LiCl and InCl3 into a zirconia tank containing zirconia balls, the ball-to-material ratio being 25:1, and using a planetary ball mill at a speed of 1000 rpm for 25 h to obtain a mixed powder;

[0030] (2) placing the mixed powder obtained in step (1) in a vacuum sealed furnace, annealing at 320° C. for 2.5 h, with a heating rate of 3° C. / min, and naturally cooling to room temperature after the annealing treatment to obtain Li3InCl6 lithium halide powder;

[0031] (3) The positive electrode material LiNi with a particle size of 3 μm 0.83 Co 0.11 Mn 0.06 O2 and Li3InCl6 lithium-conducting halide powders are placed in a resonant mixer at a mass ratio of 95:5, and resonantly mixed for 2 hours at an acceleration of 50G to obtain a positive electrode material containing a halide protective layer.

[0032] A composite positive electrode material is prepared by adopting the above preparation method.

[0033] Example 3

[0034] A preparation method of a composite positive electrode material, comprising the following steps: (1) under the protection of an argon atmosphere, weighing LiCl and YCl3 according to a stoichiometric ratio of 5:1, pouring the weighed LiCl and YCl3 into a zirconia tank containing zirconia balls, the ball-to-material ratio being 15:1, and using a planetary ball mill at a speed of 300 rpm for 20 h to obtain a mixed powder;

[0035] (2) placing the mixed powder obtained in step (1) in a vacuum sealed furnace, annealing at 280° C. for 2 h at a heating rate of 4° C. / min, and naturally cooling to room temperature after the annealing treatment to obtain Li3YCl6 lithium halide powder;

[0036] (3) The positive electrode material LiNi with a particle size of 3 μm 0.83 Co 0.11 Mn 0.06 O2 and Li3YCl6 lithium-conducting halide powders are placed in a resonant mixer at a mass ratio of 96:4, and resonantly mixed for 3 hours at an acceleration of 90G to obtain a positive electrode material containing a halide protective layer.

[0037] A composite positive electrode material is prepared by adopting the above preparation method.

[0038] Comparative Example 1

[0039] A positive electrode material, using LiNi with a particle size of 3μm 0.83 Co 0.11 Mn 0.06 O2.

[0040] test

[0041] Test 1: Impedance test.

[0042] The positive electrode materials prepared in Examples 1-3 and Comparative Example 1 were tested using an MTZ-35 electrochemical impedance analyzer with an amplitude of 100 mV and a range of 1 MHz to 1 Hz.

[0043] An all-solid-state battery is assembled using the positive electrode materials prepared in Examples 1-3 and Comparative Example 1, respectively; a method for preparing an all-solid-state battery, comprising the following steps: (1) in an argon glove box, 100 mg of a sulfide electrolyte Li6PS5Cl (Crode) is placed in a plastic sleeve with a diameter of 10 mm for a mold battery, and cold-pressed at 200 MPa to form a powder cake;

[0044] (2) 20 mg of the composite positive electrode active material powder was placed in the sleeve and cold pressed at 300 MPa on the surface of the sulfide electrolyte as a positive electrode layer. A 20 μm thick aluminum foil was stacked on the outside of the positive electrode layer to form a current collector on the outside of the positive electrode layer.

[0045] (3) placing an indium sheet with a thickness of 100 μm and a lithium sheet with a thickness of 50 μm as a negative electrode layer on the opposite side of the side where the sulfide electrolyte contacts the positive electrode layer, and allowing the negative electrode layer to further contact the sulfide electrolyte layer under a pressure of 10 MPa to obtain a laminate consisting of a positive electrode layer, a sulfide electrolyte and a negative electrode layer in sequence; stacking a copper foil with a thickness of 10 μm on the outside of the negative electrode layer, and the copper foil forms a current collector on the outside of the negative electrode layer;

[0046] The current collector formed by aluminum foil and copper foil collects and outputs the current generated by the electrode active material, which is beneficial to reduce the internal resistance of the lithium-ion battery and improve the coulombic efficiency, cycle stability and rate performance of the battery;

[0047] (4) Stainless steel current collectors are placed above and below the stack, and current collecting leads are attached to the stainless steel current collectors to obtain an all-solid-state battery.

[0048] Experiment 2: The assembled all-solid-state battery was placed in a 30℃ incubator and the LAND CT2001A battery test system was used to perform electrochemical performance tests. The cycle performance test was performed at 1C / 1C with a test voltage range of 2.0v to 3.7v.

[0049] The results of Experiment 1 and Experiment 2 are shown in Table 1.

[0050] Table 1 Test results of Experiment 1 and Experiment 2 of Examples 1-3 and Comparative Example 1

[0051]

[0052] It can be seen that by using lithium halide as an interface regulator instead of as a separator and electrode electrolyte material, the side reaction between NCM and sulfide electrolyte (LPSCl) can be effectively inhibited due to the high ion / electronic conductivity of lithium halide. Compared with the traditional positive electrode material containing only NCM, the impedance of the composite positive electrode material is greatly reduced and the battery cycle performance is strong.

[0053] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing a composite positive electrode material, comprising the steps of: (1) weighing a lithium source, an A x B y Raw materials, wherein A is a metal cation and B is a halogen anion, weigh the lithium source, A x B y The raw materials are poured into a zirconia tank filled with zirconia balls, with a ball-to-material ratio of 15:1 to 30:1, and ball-milled for 10 to 30 hours using a planetary ball mill to obtain a mixed powder; (2) placing the mixed powder obtained in step (1) in a vacuum sealed furnace, annealing at 260-320° C. for 1-6 h, with a heating rate of 1-5° C. / min, and naturally cooling to room temperature after the annealing treatment to obtain LiAB halide powder; (3) placing the NCM material and the LiAB halide powder in a resonant mixer at a mass ratio of 90-99:1-10, treating the mixture at an acceleration of 30-100G, and the resonant mixing time is 0.5-3h to obtain a positive electrode material containing a halide protective layer.

2. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The lithium source includes one or more of lithium chloride, lithium hydroxide and lithium oxide.

3. The method for preparing a composite positive electrode material according to claim 1, characterized in that: Metal cation A includes Mg 2 + 、Al 3+ , Ga 3+ 、In 3+ , Sb 3+ 、Bi 3+ , Y 3+ Sc 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Pm 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3 + , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ 、Zr 4+ , Hf 4+ Cr 3+ , Fe 3+ 、Zn 2+ and Cd 2+ One or more of .

4. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The halogen anion B includes one or more of Cl, Br, I or F.

5. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the preparation method of any one of claims 1 to 4.

6. A method for preparing an all-solid-state battery, characterized in that: The composite positive electrode material is prepared by the composite positive electrode material preparation method described in any one of claims 1 to 4.

7. The method for preparing an all-solid-state battery according to claim 6, characterized in that: The steps of the preparation method of the all-solid-state battery are as follows: (1) in an argon glove box, 100-150 mg of sulfide electrolyte Li6PS5Cl (Cluder) is placed in a plastic sleeve with a diameter of 10-12 mm for a mold battery, and cold pressed at 180-220 MPa to form a powder cake; (2) 20 to 30 mg of the composite positive electrode active material powder is placed in the sleeve, and cold pressed at 280 to 320 MPa to form a positive electrode layer on the surface of the sulfide electrolyte, and a piece of aluminum foil with a thickness of 18 to 22 μm is stacked on the outside of the positive electrode layer, and the aluminum foil forms a current collector on the outside of the positive electrode layer; (3) placing an indium sheet with a thickness of 80 to 120 μm and a lithium sheet with a thickness of 40 to 60 μm as a negative electrode layer on the opposite side of the side where the sulfide electrolyte contacts the positive electrode layer, and allowing the negative electrode layer to further contact the sulfide electrolyte layer under a pressure of 10 to 15 MPa to obtain a laminate consisting of a positive electrode layer, a sulfide electrolyte and a negative electrode layer in sequence; stacking a copper foil with a thickness of 5 to 12 μm on the outside of the negative electrode layer, and the copper foil forms a current collector on the outside of the negative electrode layer; (4) Stainless steel current collectors are placed above and below the stack, and current collecting leads are attached to the stainless steel current collectors to obtain an all-solid-state battery.

8. An all-solid-state battery, characterized in that: The all-solid-state battery is prepared by the preparation method of any one of claims 6 to 7.

Citation Information

Patent Citations

  • Composite halide solid electrolyte as well as preparation method and application thereof

    CN110970667A

  • Halide solid electrolyte material, preparation method and application thereof, and all-solid-state battery

    CN117410550A

  • Solid electrolyte material and preparation method and application thereof

    CN117497836A

  • Positive pole piece, preparation method, secondary battery and electrochemical device

    CN118782735A

  • Halide and hydride-based double-layer solid electrolyte as well as preparation method and application thereof

    CN118800951A